Structure, morphology and properties of genipin-crosslinked carboxymethylchitosan porous membranes. (5th June 2016) - Fiamingo, Anderson; Campana-Filho, Sergio Paulo
Highlights: Genipin cross-linked carboxymethylchitosan membranes were prepared. Such membranes are able to adsorb as much as 500–1700% its weight in water. Lightly cross-linked membranes presented superior mechanical properties. Lightly cross-linked membranes are more susceptible to lysozyme degradation. Abstract: Highly porous genipin cross-linked membranes of carboxymethylchitosan exhibiting different crosslinking degree (3% < CrD ¯ < 18%) were produced by using different concentrations of genipin and carboxymethylchitosan possessing high, medium or low molecular weight. The membranes were able to adsorb high amounts of PBS and presented high ultimate tensile strength and elongation-at-break the lower the crosslinking degree and the higher the molecular of the parent carboxymethylchitosan. Particularly, the membrane prepared from high molecular weight carboxymethylchitosan displayed higher swelling ratio (17.5 g/g), ultimate tensile strength (≥300 kPa) and elongation-at-break (≥65%). The susceptibility to lysozyme degradation depends only on the crosslinking degree of the membranes, the degradation rate being faster the lower the crosslinking degree. The preparation of lightly genipin cross-linked carboxymethylchitosan membranes displaying appropriated properties to fulfill specific applications as biomaterials is envisaged by using high molecular weight carboxymethylchitosan.